2020
DOI: 10.3390/ijerph17124282
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Affective, and Behavioral Constructs of COVID-19 Health Beliefs: A Comparison Between Sexual Minority and Heterosexual Individuals in Taiwan

Abstract: This online survey study aimed to compare the cognitive, affective, and behavioral constructs of health beliefs related to coronavirus disease 2019 (COVID-19) between sexual minority and heterosexual individuals in Taiwan. In total, 533 sexual minority and 1421 heterosexual participants were recruited through a Facebook advertisement. The constructs pertaining to cognition (perceived relative susceptibility to COVID-19, perceived COVID-19 severity, having sufficient knowledge and information on COVID-19, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…This study also happened to be the only study where COVID-19 related anxiety was highest in men (Balkhi et al, 2020). In the studies assessing physical activity Systematic Review: Sex-and gender-sensitive research on mental health during COVID-19 (Pillay et al, 2020;Vanni et al, 2020), hospitalization (Lassale et al, 2020), and belief in having sufficient knowledge about COVID-19 (Ko et al, 2020), men showed higher scores (in the sense of having more confidence) than women. A few other studies assessing physical activity and belief showed no sex or gender differences.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This study also happened to be the only study where COVID-19 related anxiety was highest in men (Balkhi et al, 2020). In the studies assessing physical activity Systematic Review: Sex-and gender-sensitive research on mental health during COVID-19 (Pillay et al, 2020;Vanni et al, 2020), hospitalization (Lassale et al, 2020), and belief in having sufficient knowledge about COVID-19 (Ko et al, 2020), men showed higher scores (in the sense of having more confidence) than women. A few other studies assessing physical activity and belief showed no sex or gender differences.…”
Section: Resultsmentioning
confidence: 91%
“…A few other studies assessing physical activity and belief showed no sex or gender differences. Perceived high susceptibility to COVID-19 was mostly more prevalent in women or no sex-or gender differences were observed; only in one case did men report higher scores (Ko et al, 2020). Time spent with COVID-19 news was assessed three times (in two studies, women reported higher scores, one study found no difference).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Following an extensive review of the literature, the leading research team developed the first draft of the questionnaire. Several sources were used to generate a pool of questions considered to be relevant to the study objectives 11 , 18 , 19 , 20 . A panel of eight experts, including four health education specialists, two specialist physicians in infectious diseases, an epidemiologist, and a psychologist evaluated the content validity of the questionnaire in the next step.…”
Section: Methodsmentioning
confidence: 99%
“…In many cases their palliative/end-of-life care may be compromised amidst systemic inequality, health disparity and marginalization [ 8 ]. Moreover, it has been observed that sexual minority group possesses lower perceived susceptibility to COVID-19, lesser worry about the pandemic and are less likely to undertake hygienic measures than heterosexuals [ 9 ]. Thus, proactive awareness campaign for COVID-19 to specifically highlight the health needs of LGBTQ community is necessary from the healthcare providers and social workers [ 10 ].…”
mentioning
confidence: 99%